Pengembangan LKPD pada Materi Teks Laporan Hasil Observasi Berbasis TGT (Team Games Tournaments) untuk Meningkatkan HOTS Siswa Kelas X - Widyastuti, Rizky; Rita, Rita; Safina, Nila; Kartika, Rika; Soraya, Ratna (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2025)
This study aims to develop and evaluate the feasibility and effectiveness of a TGT-based LKPD (Student Worksheet) integrated with Wordwall media for teaching observation report texts to enhance higher-order thinking skills (HOTS) in 10th-grade students. Utilizing the Research and Development (R&D) approach with the ADDIE model—Analyze, Design, Develop, Implement, and Evaluate—the study systematically assessed the instructional material. The findings indicate that the developed LKPD was deemed highly feasible, receiving ratings of 82% and 87% from material experts and 84% and 86.89% from design experts. Field trials demonstrated a significant improvement in students' HOTS, achieving an effectiveness score of 83.60%. These results confirm that the integration of TGT-based learning with Wordwall media enhances student engagement and comprehension, making it an effective instructional tool for fostering critical thinking skills in language learning.